The Potential of Sonneratia caseolaris Mangrove Plant as Functional Food and Medicine - Audah, Kholis Abdurachim; Siti Anisa, Amalda (Swiss German University & Perhimpunan Penggiat Pangan Fungsional dan Nutrasetikal Indonesia (P3FNI), 2024)
Mangrove forests are a unique ecosystem found extensively in tidal areas along coastal regions, including Indonesia. Apart from their environmental potential, these plants have also been proven to play a role in various functional foods with potential medicinal properties. One such plant is the Sonneratia caseolaris mangrove, commonly known as the mangrove apple S. caseolaris grows at a depth of 18-22 cm, in flooded areas directly facing the coastline. Despite its abundance, people rarely consume this plant directly due to its sour taste and the lack of knowledge about its chemical compounds, hindering its optimal utilization. This research aims to conduct an article review on studies of S. caseolaris mangroves to provide information that can enhance public awareness, particularly regarding its benefits and processed products. The method employed includes a review of national and international articles using search engines such as Google Scholar, Google Advanced Search, INPL database, Citizen Medicine (CitMed) and other publication websites. The research findings demonstrate that S. caseolaris contains beneficial compounds such as flavonoids, alkaloids, tannins, and phenols in its stem bark, leaves, and fruits. Its processed products can be packaged as dodol, beverages or herbal teas. Apart from food products, this plant is also used in topical preparations such as sunscreen powder, face mist, and clay masks. These results indicate that S. caseolaris is safe for consumption in various products, thus allowing for its maximum utilization.